Mental health stigma in adolescents: a scoping review - Carla Elizalde-Resano; Charo Reparaz; Belén Ochoa-Linacero (Psychology, Society & Education)
Introduction. Mental health disorders are increasingly common in adolescence, and peer stigma represents a significant barrier. Defining this construct is essential for its evaluation, prevention, and intervention. The aim of this study was to conceptualize mental disorder stigma in adolescents. Method. A scoping review was conducted in the Web of Science, Scopus, Eric, PubMed, and PsycInfo databases (2011-2021), using descriptors in both English and Spanish. A total of 11,144 articles were retrieved; 51 were selected after screening, and six additional articles were included through other methods. Results. Social stigma in adolescents is described as negative beliefs that may lead to rejection and discriminatory behavior. Different types were identified (public stigma, self stigma, structural stigma, and associative stigma). Stigma is considered a multidimensional construct (cognitive, emotional, and behavioral dimensions) and is influenced by variables such as sex, nationality, educational level, age, socioeconomic status, personal experience, mental health literacy, and help-seeking behavior. Discussion. Most studies are grounded in the theoretical contributions of Goffman and Corrigan. Recent literature highlights the urgent need to develop effective, sustainable, and culturally adapted prevention programs. The lack of consensus on conceptual and methodological frameworks hinders comparison across studies, reinforcing the importance of valid instruments tailored to adolescents. Identifying factors that influence stigma is essential to guide more inclusive educational interventions.